2014
DOI: 10.1111/raq.12072
|View full text |Cite
|
Sign up to set email alerts
|

Shrimp‐based livelihoods in mangrove silvo‐aquaculture farming systems

Abstract: The paper reviews the following three types of mangrove-shrimp systems: (i) integrated with canals between platforms planted with mangrove; (ii) associated having larger areas of water and a large mangrove area; and (iii) separated, with a dyke separating ponds from forest. The variations in shrimp yield of integrated and associated systems, that is, mixed systems, are attributable to water exchange, % water surface, primary production, stocking of post-larvae, leaf litter fall and decomposition, species, cove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 68 publications
1
51
1
1
Order By: Relevance
“…Dedicated efforts to restore and maintain mangrove have been implemented in Vietnam, inclusive of a policy program supporting integrated mangrove shrimp farming (IMS). IMS can be economically viable and allow for sufficient ecological quality [43], particularly compared to extensive shrimp systems [30]. However, it has been observed that farmers who practice extensive farming do not adopt IMS voluntarily.…”
Section: Developing a Serious Game Within The Assessing The Learningmentioning
confidence: 99%
“…Dedicated efforts to restore and maintain mangrove have been implemented in Vietnam, inclusive of a policy program supporting integrated mangrove shrimp farming (IMS). IMS can be economically viable and allow for sufficient ecological quality [43], particularly compared to extensive shrimp systems [30]. However, it has been observed that farmers who practice extensive farming do not adopt IMS voluntarily.…”
Section: Developing a Serious Game Within The Assessing The Learningmentioning
confidence: 99%
“…Secara umum masyarakat sekitar mangrove tidak memiliki kemampuan untuk beralih mata pencaharian karena keterbatasan kemampuan dan rendahnya tingkat pendidikan (Hussain & Badola, 2010). Penyediaan alternatif mata pencaharian yang memberikan penghidupan yang layak bagi masyarakat lokal diperlukan untuk mendukung usaha pelestarian ekosistem mangrove (Ahmad, 2009;Bosma, Nguyen, Siahainenia, Tran, & Tran, 2016;Karlina, Kusmana, Marimin, & Bismark, 2016).…”
Section: Nilai Ekonomi Total Mangroveunclassified
“…Respondents said that to support a family, an IMS farm had to cover at least 2 ha. The literature mentions an even larger area requirement, of 4 to 6 ha (Bosma et al, 2014). This variation may be due to the different sizes of IMS farms found in the different research areas.…”
Section: Difficulties Farmers Had With the Ims Systemmentioning
confidence: 99%
“…These mixed systems incorporate mangrove planting in and around ponds for shrimp culture, or on bunds or platforms on the ponds. IMS farming contributes more to biodiversity than other shrimp farming systems (Bosma et al, 2014). However, despite the benefits of these integrated systems, their uptake has been slow.…”
Section: Introductionmentioning
confidence: 99%